The effect of mobile phone text-message reminders on Kenyan health workers' adherence to malaria treatment guidelines: A cluster randomised trial - Zurovac, D; Sudoi, R; Akhwale, W; Ndiritu, M; Hamer, D; Rowe, A; Snow, R (2011)
Health workers' malaria case-management practices often differ from national guidelines. We assessed whether text-message reminders sent to health workers' mobile phones could improve and maintain their adherence to treatment guidelines for outpatient paediatric malaria in Kenya. From March 6, 2009, to May 31, 2010, we did a cluster-randomised controlled trial at 107 rural health facilities in 11 districts in coastal and western Kenya. With a computer-generated sequence, health facilities were randomly allocated to either the intervention group, in which all health workers received text messages on their personal mobile phones on malaria case-management for 6 months, or the control group, in which health workers did not receive any text messages. Health workers were not masked to the intervention, although patients were unaware of whether they were in an intervention or control facility. The primary outcome was correct management with artemether-lumefantrine, defined as a dichotomous composite indicator of treatment, dispensing, and counselling tasks concordant with Kenyan national guidelines. The primary analysis was by intention to treat. The trial is registered with Current Controlled Trials, ISRCTN72328636. 119 health workers received the intervention. Case-management practices were assessed for 2269 children who needed treatment (1157 in the intervention group and 1112 in the control group). Intention-to-treat analysis showed that correct artemether-lumefantrine management improved by 23·7 percentage-points (95 CI 7·6-40·0; p=0·004) immediately after intervention and by 24·5 percentage-points (8·1-41·0; p=0·003) 6 months later. In resource-limited settings, malaria control programmes should consider use of text messaging to improve health workers' case-management practices. The Wellcome Trust. © 2011 Elsevier Ltd.